Taxonomic notes on the genera Brypoctia Schoorl, 1990 and Schreiteriana Fletcher & Nye, 1982 (Lepidoptera, Cossidae) - Penco, Fernando C.; Yakovlev, Roman V.; Witt, Thomas J. (Zootaxa, 2016)
Currently, the Cossidae of South America are rather poorly studied. Data on the distribution and taxonomy of Neotropical carpenter moths are lacking. An exception is the clarification of the taxonomic position of the genus Miacora Dyar, 1905 (Yakovlev 2014), Neotropical Cossidae checklist (Donahue 1995), and a preliminary list of Cossidae of Argentina (Penco & Yakovlev 2015). The majority of Neotropical Cossidae genera have not been studied and the taxonomic position of some genera remains completely unresolved. Additionally, images of genitalia of the Neotropical genera have not been published, including the genera Brypoctia Schoorl, 1990 and Schreiteriana Fletcher & Nye, 1982 (Cossidae: Zeuzerinae). The taxonomic position of the second genus was questioned by Schoorl (1990).